Interaction effects of alcohol consumption and dizziness/vertigo on fall risk in psychiatric Inpatients: a cross-sectional study - Peng, Jing; Liao, Huixia; Liu, Qin; Qin, Yuan; He, Xubin; Gong, Yanlin; Dong, Tiaoxia; Zhang, Chengcheng; Yu, Jianghong; Wang, Shengjun; Zuo, Juntao; Long, Jianmei; et al. (Frontiers in Psychiatry, 2026)
BackgroundPatients with mental disorders have a high incidence of falls and fall-related injuries, and although a history of alcohol consumption and dizziness/vertigo symptoms are assessed at the admission stage, their combined effect on fall risk has not been adequately quantified.ObjectivesThis exploratory study aimed to investigate the potential interaction between a history of alcohol consumption and dizziness/vertigo on the occurrence of falls among patients with mental disorders.MethodsA cross-sectional study was conducted among patients hospitalized in a psychiatric specialty hospital. Patients were divided into fall and non-fall groups. Data were analyzed using a Chi-square test and Multivariate logistic regression. Multiplicative and additive models were applied to calculate the interactions of a history of alcohol consumption and dizziness/vertigo, respectively.Results2210 participants were included, 194 in the falls group and 2016 in the non-falls group. Multivariate analysis demonstrated that the utilization of antiepileptic medication, a history of alcohol consumption, dizziness/vertigo, body mass index (BMI) and diagnostic type were independent risk factors for falls in patients diagnosed with mental disorders. The multiplicative interaction analysis revealed a statistically significant interaction between a history of alcohol consumption and the presence of dizziness/vertigo on the incidence of falls among patients with mental disorders, after controlling for relevant variables(P<0.05). The additive interaction results suggested that the relative excess risk due to interaction (RERI), the attributable proportion due to interaction (API), and the synergy index (SI) were 7.470 (95% CI: 2.701-12.239), 0.674 (95% CI: 0.511-0.838), and 3.864 (95% CI: 2.040-7.320) after adjusting for relevant variables.ConclusionThere is a potential positive interaction between a history of alcohol consumption and dizziness/vertigo on the occurrence of falls in patients with mental disorders. Given the exploratory nature of this study and the small sample size of the co-exposed group, this conclusion requires validation in larger, prospective studies.